L’ordine della natura e la struttura del linguaggio - Di Prospero, Alfonso (Filosofia, 2019)
In this paper the relationship between the issue of induction and the patterns of communication will be inquired. The basic idea is that the process of communication is intrinsically linked with the use of the topic-comment structure, and this linguistic pattern conducts the human mind to retain that the reality is ontologically organized in substances (or individuals) and accidents (or more generally, properties). It is proposed that the ontological meaning of the laws of nature can be better explained by the attempt to show that other patterns of thought are available. So it will be proposed a semantics that is based more substantially on names, and not on propositions or topic-comment structures. Our instinctive trust in laws of nature is interpreted as the consequence of the ontological connections between the respective references of the names. Some ideas of Emanuele Severino are put in comparison with this theoretical sketch.